Rhetoric of Arts’ Boundaries in the 1960s and the Establishing of Postmedial Installation Art - Makeeva, Svetlana O. (Actual Problems of Theory and History of Art, 2025)
The 1960s mark one of key milestones in Modernist art history and theory. At that time the question of the medium, or art itself, was discussed especially actively. On the one hand, such influential critics as Clement Greenberg or his disciple Michael Fried supported the idea of aesthetic autonomy and clear boundaries between the arts. The purity of the arts was to be secured by narrowing their “area of competence”and revealing the essence of their medium (which equals to the medium-specificity principle). On the other hand, leading Minimalist artists (Donald Judd, Tony Smith) as well as those working with environments and happenings (Allan Kaprow, first of all), challenged not only the boundaries between the arts, but also the art-and-life boundary. The above mentioned discussion is especially interesting with relation to the establishing of installation art which took about a decade, from 1965 to 1975. Installation has been one of the artforms central to contemporary art; notably, Rosalind Krauss describes installation art as “multimedial”,“intermedial” or “postmedial”. Intermediality, which in this paper is understood as the quality of combining features of traditional arts — spatial and temporal, — is often considered by some installation researchers (Juliane Rebentisch, Anne Ring Petersen) to be its distinctive mark. Michael Fried’s criticism of Minimalism,“theatricality” and mixing the arts, laid out in Art and Objecthood, turned out to be a neat characterization of“installational” thinking and vision in art. The majority of those whose art Fried called “theatrical” are now seen as installation art’s precursors or pioneers.
Keywords: installation; environment; painting; Modernism; intermediality; theatricality; Minimalism; medium; aesthetic autonomy; Clement Greenberg; Michael Fried; Rosalind Krauss; 1960s; 1970s